Bone morphogenetic protein 2 inhibits growth differentiation factor 8-induced cell signaling via upregulation of gremlin2 expression in human granulosa-lutein cells - Xiaoyan Luo; Hsun-Ming Chang; Yuyin Yi; Yingpu Sun; Peter C. K. Leung (BMC, 2021)
Abstract Background Bone morphogenetic protein 2 (BMP2), growth differentiation factor 8 (GDF8) and their functional receptors are expressed in human ovarian follicles, and these two intrafollicular factors play essential roles in regulating follicle development and luteal function. As BMP antagonists, gremlin1 (GREM1) and gremlin2 (GREM2) suppress BMP signaling through blockage of ligand-receptor binding. However, whether BMP2 regulates the expression of GREM1 and GREM2 in follicular development remains to be determined. Methods In the present study, we investigated the effect of BMP2 on the expression of GREM1 and GREM2 and the underlying mechanisms in human granulosa-lutein (hGL) cells. An established immortalized human granulosa cell line (SVOG) and primary hGL cells were used as study models. The expression of GREM1 and GREM2 were examined following cell incubation with BMP2 at different concentrations and time courses. The TGF-β type I inhibitors (dorsomorphin, DMH-1 and SB431542) and small interfering RNAs targeting ALK2, ALK3, SMAD2/3, SMAD1/5/8 and SMAD4 were used to investigate the involvement of the SMAD-dependent pathway. Results Our results showed that BMP2 significantly increased the expression of GREM2 (but not GREM1) in a dose- and time-dependent manner. Using a dual inhibition approach combining kinase inhibitors and siRNA-mediated knockdown, we found that the BMP2-induced upregulation of GREM2 expression was mediated by the ALK2/3-SMAD1/5-SMAD4 signaling pathway. Moreover, we demonstrated that BMP2 pretreatment significantly attenuated the GDF8-induced phosphorylation of SMAD2 and SMAD3, and this suppressive effect was reversed by knocking down GREM2 expression. Conclusions Our findings provide new insight into the molecular mechanisms by which BMP2 modulates the cellular activity induced by GDF8 through the upregulated expression of their antagonist (GREM2).